Polymodal Sensory Transduction in Mouse Corneal Epithelial Cells - Lapajne, Luka (Invest Ophthalmol Vis Sci, 2020)
PURPOSE: Contact lenses, osmotic stressors, and chemical burns may trigger severe discomfort and vision loss by damaging the cornea, but the signaling mechanisms used by corneal epithelial cells (CECs) to sense extrinsic stressors are not well understood. We therefore investigated the mechanisms of swelling, temperature, strain, and chemical transduction in mouse CECs. METHODS: Intracellular calcium imaging in conjunction with electrophysiology, pharmacology, transcript analysis, immunohistochemistry, and bioluminescence assays of adenosine triphosphate (ATP) release were used to track mechanotransduction in dissociated CECs and epithelial sheets isolated from the mouse cornea. RESULTS: The transient receptor potential vanilloid (TRPV) transcriptome in the mouse corneal epithelium is dominated by Trpv4, followed by Trpv2, Trpv3, and low levels of Trpv1 mRNAs. TRPV4 protein was localized to basal and intermediate epithelial strata, keratocytes, and the endothelium in contrast to the cognate TRPV1, which was confined to intraepithelial afferents and a sparse subset of CECs. The TRPV4 agonist GSK1016790A induced cation influx and calcium elevations, which were abolished by the selective blocker HC067047. Hypotonic solutions, membrane strain, and moderate heat elevated [Ca(2+)](CEC) with swelling- and temperature-, but not strain-evoked signals, sensitive to HC067047. GSK1016790A and swelling evoked calcium-dependent ATP release, which was suppressed by HC067027 and the hemichannel blocker probenecid. CONCLUSIONS: These results demonstrate that cation influx via TRPV4 transduces osmotic and thermal but not strain inputs to CECs and promotes hemichannel-dependent ATP release. The TRPV4-hemichannel-ATP signaling axis might modulate corneal pain induced by excessive mechanical, osmotic, and chemical stimulation.